Demographic Factors and their Relation to Fatigue and Mental Disorders in 12-Hour Petrochemical Shift Workers - Ahmad Bazazan; Yahya Rasoulzadeh; Iman Dianat; Abdolrasoul Safaiyan; Zohreh Mombeini; Ehsan Shiravand (Health Promotion Perspectives, 2014)
Background: Shift workers may be exposed to fatigue and mental disorders due to various work-related risk factors. This study evaluated the impact of demographic characteristics on fatigue and mental disorders among 12-hour shift workers in petrochemical industries. Methods: This study was conducted among 290 shift workers of Pardis Petrochemical Company in Iran. Data were collected using a general questionnaire for the demographic characteristic as well as multidimensional fatigue inventory (MFI-20) and general health questionnaire (GHQ-28). Results: Married workers were less likely to suffer from reduced activity levels (P< 0.027), depression (P< 0.032) and mental disorders (P< 0.040). Social dysfunction score (P< 0.029) and mental disorders (P< 0.048) decreased with shift work experience. Shift workers with non-academic education less likely to suffer from reduced activity levels (P< 0.000) and mental fatigue (P< 0.028). Conclusion: Despite the significant difference between the variables, this study showed a weak effect of individual and occupational demographic characteristics on fatigue and mental disorders.